ANALISIS PENGARUH ROE, UKURAN PERUSAHAAN, TINGKAT INFLASI DAN TINGKAT KURS TERHADAP RETURN SAHAM - Frihardina Marsintauli (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2019)
The infrastructure development is one of the supporting factors in the movement of a economic country. For over the past four years, the government has been focus on building transportation infrastructure and utilities as they believe that expanding infrastructure can contribute to economic growth and investment later. There is an increase in companies in the infrastructure, utilities and transportation sectors from 2016 to 2018, there were an increase in 24 public companies. This proves that investment in the infrastructure, utilities and transportation sectors is considered to be very proftable for investors. The purpose in this study is to empirically study the eﬀect of fnancial performance (Return On Equity), size, inﬂation rate and exchange rate on stock returns of infrastructures, utilities and communications company listed on the Indonesia Stock Exchange in observations from 2016-2018 using multiple regression method with SPSS. This study is using secondary data from Indonesia Stock Exchange (JSX) Yearly Statistics, ofcial website of Bank Indonesia, website Yahoo Finance on 2016-2018. Population research consists of 75 listed companies and fnal result with purposive sampling method for this research by using 24 companies. The hypothesis test result showed that ROE have positive inﬂuence to stock return and on the other hand there is no signifcantly inﬂuence for size’s company, inﬂation and exchange rate.